STEM-BASED FACILITATOR IN WEATHER OBSERVATION TO DETERMINE PRAYER TIME - Siregar, Nur Choiro; Anggrayni, Dewi (Universitas Tadulako, 2023)
Detecting whether with tools based on science, technology, engineering, and mathematics (STEM) is one of the tools that can be used to determine prayer times for people who are in small (backward) villages. The objective of this study is to facilitate the people of Situpete village to determine prayer times through science, technology, engineering, and mathematics (STEM). This research method uses qualitative involving five people. The data and data sources used are in-depth interviews and observations. The results of the interview are analyzed with these techniques. The results of this study found that with assembly using PVC pipes, Coaxial cables type RG58, Terminal Blocks, PCB boards, Sound Cards, RPI, and LCD the community became educated in determining the time of prayer through STEM-based weather detection tools. Not only that, but the community can also use the tool themselves to determine the time of prayer according to weather conditions in the Kampung Situpete environment. Educational themes felt by the community such as (1) the need for equipment, (2) accessibility, and (3) technological knowledge. Implication: the integration of STEM learning is very important to be carried out in schools to educate the public in meeting their daily needs. Teachers (academic circles) need to emphasize that STEM science is not only studied as a theory but is important to apply in real life. Future studies should use simpler tools at a lower cost and use more study participants.